Distribution of Cd, Pb and Cu between dissolved fraction, inorganic particulate and phytoplankton in seawater of Terra Nova Bay (Ross Sea, Antarctica) during austral summer 2011–12. (October 2017) - Illuminati, S.; Annibaldi, A.; Romagnoli, T.; Libani, G.; Antonucci, M.; Scarponi, G.; Totti, C.; Truzzi, C.
Abstract: During the austral summer 2011–2012, the metal quotas of Cd, Pb and Cu in the phytoplankton of Terra Nova Bay (TNB, Antarctica) were measured for the first time. Evolution of all the three metal distributions between dissolved and particulate fractions during the season was also evaluated. Metal concentrations were mainly affected by the dynamic of the pack ice melting and phytoplankton activity. In mid-December when TNB area was covered by a thick pack ice layer and phytoplankton activity was very low, all the three metals were present mainly in their dissolved species. When the pack ice started to melt and the water column characteristics became ideal (i.e. moderate stratification, ice free area), the phytoplankton bloom occurred. Cd showed a nutrient-type behaviour with dissolved and particulate fractions mainly influenced by phytoplankton activity. Cd quota showed a mean value of 0.12 ± 0.07 nmol L −1 (30–100% of the total particulate). Also Cu showed a nutrient-type behaviour, with its quota in phytoplankton varying between 0.08 and 2.1 nmol L −1 (20–100% of the total particulate). Pb features the typical distribution of a scavenged element with very low algal content (0.03 ± 0.02 nmol L −1, representing 20–50% of the total particulate). The vertical distribution of this element was influenced by several factors (e.g. pack ice melting, atmospheric inputs), the phytoplankton activity affecting Pb behaviour only partially. Metal:C ratios provide valuable information on the biological requirements for Cd, Pb and Cu, leading us to better understand their biogeochemical cycles. Highlights: First direct measurements of metal quotas in phytoplankton from Antarctica. Metal distribution between dissolved, inorganic and algal particulate. Metals affected by pack ice dynamics and phytoplankton activity. Metal:C ratios provide valuable information on trace metal requirements.